2017
DOI: 10.1002/phar.1989
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Adherence and Persistence with Direct Oral Anticoagulants in Adults with Atrial Fibrillation

Abstract: BACKGROUND Evidence of adherence and persistence patterns in anticoagulation (AC) therapy comparing treatment-na€ ıve and non-na€ ıve patients is lacking. The objective of this study was to evaluate patterns of medication adherence and persistence in a real-world setting among AC-na€ ıve and ACexperienced patients with atrial fibrillation (AF) who were treated with direct oral anticoagulants (DOACs). METHODS AF patients newly initiating a DOAC with a minimum of 6 months of continuous health plan enrollment pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
73
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 35 publications
12
73
2
5
Order By: Relevance
“…For instance, concerns have been raised about use of DOACs among patients with kidney disease, because impaired renal function may lead to DOAC accumulation and increased bleeding risk (Lega et al , ). Compliance to DOACs in real‐world settings may also be poorer than typically exhibited among RCT participants (Tsai et al , ; Shore et al , , ; Garkina et al , ; Manzoor et al , ). Furthermore, no VTE RCTs have conducted comparisons between DOACs.…”
mentioning
confidence: 99%
“…For instance, concerns have been raised about use of DOACs among patients with kidney disease, because impaired renal function may lead to DOAC accumulation and increased bleeding risk (Lega et al , ). Compliance to DOACs in real‐world settings may also be poorer than typically exhibited among RCT participants (Tsai et al , ; Shore et al , , ; Garkina et al , ; Manzoor et al , ). Furthermore, no VTE RCTs have conducted comparisons between DOACs.…”
mentioning
confidence: 99%
“…Despite the emergence of the direct oral anticoagulants (DOAC), warfarin is still one of the mainstay oral anticoagulants used to treat over 4 million patients in the United States and over 40 000 outpatient prescriptions are being written annually . Indicated for primary and secondary prevention of venous and arterial thrombosis, warfarin does not come without challenges, primarily stemming from maintenance of patients' international normalized ratio (INR) within a narrow therapeutic window .…”
Section: Introductionmentioning
confidence: 99%
“…Indicated for primary and secondary prevention of venous and arterial thrombosis, warfarin does not come without challenges, primarily stemming from maintenance of patients' international normalized ratio (INR) within a narrow therapeutic window . Given that recent data suggest that DOAC users may have suboptimal adherence and persistence over time, and individuals with renal dysfunction or mechanical heart valves will still require treatment with warfarin therapy, it is important to continually assess contemporary practice models that optimize anticoagulation‐related clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most published series, only about 60% of patients with a CHA 2 DS 2 -VASc score of ≥2 are prescribed oral anticoagulation 5 6. Recent work examining the persistence of therapy in patients with AF who are prescribed a novel oral anticoagulant agent showed that at 1 year only 30%–50% remained on therapy 7. The operative question is: are we failing our patients or are our patients making well-informed decisions about their own care (taking into account their own values and personal finances) that happen to frequently diverge from the guidelines?…”
mentioning
confidence: 99%